Arte tumular no interior do Estado de São Paulo: Araraquara - Ferreira, Nathalia dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This study have as objetive the understanding of tumular art how national artistic heritage, and the cemetery as a protective organ of this kind of art – as a discussion on the work of heritage preservation organs. Therefore, in addition to a brief journey on tomb art and its origins, the research investigated issues such as memory and cultural heritage and made a case study on tumular art in the state of São Paulo, particularly in the city of Araraquara. The objective was to seek a reflection on these works as elements of an artistic order, discussing the effect they exert on the viewer, as well as the social functions added to them and the rescue of their symbologies.

Este trabalho tem como objetivo o estudo e entendimento da arte tumular como patrimônio artístico nacional, e do cemitério como um órgão protetor dessa arte – como uma discussão sobre o trabalho dos órgão de preservação patrimonial. Para tanto, além de um breve percurso sobre a arte tumular e suas origens, a pesquisa investigou questões como memória e patrimônio cultural e fez um estudo de caso sobre a arte tumular do estado de São Paulo em particular da cidade de Araraquara. O objetivo foi buscar uma reflexão dessas obras como elementos de ordem artística, discorrendo sobre o efeito que exercem no espectador, assim como as funções sociais adicionadas a elas e o resgate de suas simbologias
Tumular art in the interior of the State of São Paulo: Araraquara
Keywords: Tumular art; National heritege; Phenomenology; Arte tumular; Patrimônio nacional; Fenomenologia; Araraquara (SP); Tumulos - Arte